2017
DOI: 10.1097/bcr.0000000000000372
|View full text |Cite
|
Sign up to set email alerts
|

Post Junctional Sudomotor and Cutaneous Vascular Responses in Noninjured Skin Following Heat Acclimation in Burn Survivors

Abstract: Thermal tolerance is improved in burn survivors following 7 days of exercise heat acclimation. It is unknown whether post-junctional sudomotor and/or cutaneous vascular adaptations in non-injured skin contribute to this improvement. Thirty-three burn survivors were stratified into moderately (17-40% BSA grafted, n = 19) and highly (>40% BSA grafted, n = 14) skin grafted groups. Nine non-burned subjects served as controls. All subjects underwent a 7 day heat acclimation protocol, which improved thermal toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…2009a,b; Lorenzo & Minson, 2010; Pearson et al . 2017) and primates (Sato et al . 1990), only two studies have provided indirect evidence of central thermoregulatory adaptations following heat acclimation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2009a,b; Lorenzo & Minson, 2010; Pearson et al . 2017) and primates (Sato et al . 1990), only two studies have provided indirect evidence of central thermoregulatory adaptations following heat acclimation.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, these initial findings served as the basis for future studies attempting to more directly delineate peripheral vs. central thermoregulatory adaptations following heat acclimation. Although direct evidence for peripheral modifications of the thermoeffector organs have been demonstrated in humans (Inoue et al 1999;Buono et al 2009a,b;Lorenzo & Minson, 2010;Pearson et al 2017) and primates (Sato et al 1990), only two studies have provided indirect evidence of central thermoregulatory adaptations following heat acclimation. These studies reported a greater sweat gland expulsion frequency, a proposed marker of central sudomotor activity, following heat acclimation (Ogawa & Sugenoya, 1993) and seasonal acclimatization (Taniguchi et al 2011).…”
Section: Peripheral Vs Central Mechanisms Of Human Heat Adaptationmentioning
confidence: 99%
See 2 more Smart Citations
“…While others have furthered the understanding of temperature regulation in burned adults during passive heating [12,13,18,26,54,57,58] and exercise heat stress [21,22,43,53,54], none have studied heat exchange at rest in burned children and only a few (work from our laboratory, [33,34]) have investigated exercise heat stress in burned children. To our knowledge, this is the first study characterizing skin blood flow responses to local heating in burned and non-burned children.…”
Section: Perspectivementioning
confidence: 99%